PREVALENCE OF ANEMIA AMONGST WOMEN OF REPRODUCTIVE AGE (The Research of Medical Science Review, 2024)
Background: Anemia causes high rates of morbidity and death in mothers and infants, making it a serious public health problem for women of reproductive age. Anemia is a condition in which the hemoglobin concentration or the quantity and size of red blood cells fall below a certain threshold, hence reducing the blood's ability to carry oxygen throughout the body. Objective: To determine the frequency of anemia amongst women of their reproductive age at our setting. Methodology: This cross-sectional study was carried out at the Department of Medicine CMH Abbottabad. The study duration was one year from November 2022 to November A total of 200 women of reproductive age were included in the current study. The inclusion criteria for our study were all the women in the reproductive age (15-40 years) and both married and unmarried women. All the data was collected by using a specialized questionnaire developed for this study. All the data was analyzed by using SPSS version 24. Results: In the current study, a total of 200 women were enrolled based on inclusion criteria. The means age (±Standard deviation) of participants was 29 (±8.11) years. The frequency of anemia in our study participants was 140 (70%). Based on the type of anemia, the microcytic anemia was observed in 100 (50%) participants while macrocytic anemia was observed in 40 (20%) participants. Conclusion: Our study concludes that the frequency of anemia amongst women of reproductive age is high. These results highlight the need for focused interventions to alleviate anemia in this population, especially in pregnant women, younger women, and women from lower socioeconomic backgrounds.